Rancangan Sistem Manajemen K3 Berdasarkan OHSAS 18001:2007 - Jeni Yusup Wijana; Aviasti; Satori, Mohamad (UNISBA Press, 2024)
Abstract. At present at PT Elco Indonesia Sejahtera (PT. EIS) there is a phenomenon of complaints from employees regarding non-ergonomic work positions, unsafe equipment arrangements, high rates of work accidents, irregular housekeeping on the production floor, the absence of Standard Operating Procedures, and the absence of an Occupational Safety and Health organization. Based on the existing phenomena, it turns out that PT EIS has not implemented an Occupational Safety and Health Management System. The purpose of this research is to design an Occupational Safety and Health Management System based on the OHSAS 18001 standard. This research uses a descriptive qualitative approach with interview, observation, and documentation techniques. The results of the required research include the design of legal requirements, the design of the Occupational Safety and Health Advisory Committee team, emergency response team, Standard Operating Procedures, inspection document forms, and management review documents. These designs were developed by taking into account the specific needs and characteristics of tanneries, with the aim of increasing awareness and compliance with occupational safety and health norms. Abstrak. Pada saat ini di PT Elco Indonesia Sejahtera (PT. EIS) terdapat fenomena keluhan dari karyawan mengenai posisi kerja yang tidak ergonomis, penataan peralatan yang tidak aman, tingginya angka kecelakaan kerja, ketidakteraturan housekeeping di lantai produksi, ketiadaan Standar Operasional Prosedur (SOP), dan ketiadaan organisasi K3. Berdasarkan fenomena yang ada, ternyata di PT ElS belum menerapkan Sistem Manajemen K3. Tujuan penelitian ini adalah merancang Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) berdasarkan standar OHSAS 18001. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik wawancara, observasi, dan dokumentasi. Hasil penelitian yang diperlukan meliputi rancangan persyaratan hukum, rancangan tim Panitia Pembina Keselamatan dan Kesehatan Kerja (P2K3), tim tanggap darurat, Standar Operasional Prosedur (SOP), formulir dokumen pemeriksaan, dan dokumen tinjauan manajemen. Rancangan ini dikembangkan dengan memperhatikan kebutuhan dan karakteristik khusus perusahaan penyamakan kulit, dengan tujuan meningkatkan kesadaran dan kepatuhan terhadap norma keselamatan dan kesehatan kerja.